Rab35 controls cilium length, function and membrane composition - Kuhns, Stefanie (2022)
8021-00425B) to JSA, by a postdoctoral fellowship from FCT (SFRH/BPD/32323/2006) to CS and by iNOVA4Health—UID/Multi/ 04462/2013, a program financially supported by FCT/Ministério da Educação e Ciência, through national funds and co-funded by FEDER under the PT2020 Partnership Agreement. This article is supported by the LYSOCIL project. This project has received funding from the European Union’s Horizon 2020 research and innovation programme under grant agreement No 811087.